Naphthalene association and uptake in Pseudomonas putida. - Bateman, J N (1986)
Two methods for bacterial membrane transport, filtration and flow dialysis, were used to study cellular association of Pseudomonas putida with naphthalene. It is not technically possible to determine the exact cellular or vesicular location of the naphthalene, and because it is hydrophobic, it could be at the membrane(s) rather than inside the cells. As an index of naphthalene having crossed the inner membrane we used the intracellular formation of its first catabolite. An energized membrane or ATP was not essential for association or movement into the cell. Evidence for a nonspecific association and a movement into cells by simple diffusion are the lack of saturation of association, an absence of inhibition of association by protein inhibitors and structural analogs, and the passage of naphthalene through cell membranes in the presence of iodoacetamide. Specific naphthalene metabolism gene expression was not required for association.